Cystosonography with echocontrast: A new imaging technic for detecting vesicoureteral reflux in children - Ifran, E. K. B.; Lombay, B.; Szabo, L. (Paediatrica Indonesiana, 2017)
Vesicoureteral reflux (VUR) is a common pediatric problem. Its late consequences may cause hypertension andÂ renal failure, so that early diagnosis is important. Micturition cystourography (MCU) or radionuclide cystography (RNC) is theÂ imaging of choice but these technics expose the children 10 radiation. Cystosonography with echocontrast is a new imaging technic lor detecting VUA without exposing the children to radiation. The aim of this article is to review this technic and to showÂ our early experiences with this new method in the Pediatric Radiology Department of Borsod County Teaching Hospital,Â Miskolc, Hungary.